Neck extensor muscle weakness (dropped head syndrome) following radiotherapy - Bhatia, Sumita (Radiology and oncology (Ljubljana), 2006)
Background. Dropped head syndrome is an unusual condition in which the head cannot be held upright in its normal anatomic position secondary to pronounced, isolated, neck extensor muscle weakness. Case repori. A case of dropped head syndrome in a female with a history of radiotherapy for Hodgkin'slyrnphoma and a clinical history consistent with multiple sclerosis is presented, and potential etiologies are discussed. Conclusions. Muscular atrophy and lower motor neuron injury secondary to isolated anterior horn cellinjury from radiotherapy emerge as the most likely etiology.
Keywords: Glava; Head; Hodgkin's Disease; Middle Age; Mišična atrofija; Mišična slabost; Muscle Weakness; Muscular Atrophy; Neck; obsevanje; posledice; Radiotherapy; rak (medicina); Srednja leta; Vrat; Vrata